AB0996 Rheumathologic Diseases in Adolescence: Psychological Profile of a Difficult Age. (9th June 2015) - Maggio, M.C.; Riticella, R.; Salvo, G.; Corsello, G.
Abstract : Background: Chronic disease significantly interfere with the quality of life at every age, expecially in a period of life characterized by the need to assume a role in the society and the research of a specific identity. The personal image is often destroyed by the disease, the long term sequelae of pharmacological treatment. Adolescents are frequently obligated to quit many possibilities of experience with peers. Objectives: We realized a plurispecialistic approach to adolescents with rheumatologic diseases, with the figures of neuropsychiatric, psychologists, rheumatologists, endocrinologists, to give an answer to the complex requests of these patients. Methods: We evaluated 20 patients with rheumatologic diseases (JIA; SLE; Bechet Disease; Autoinflammatory syndromes…) and we used psychological tests as the Physique Anxiety Scale, the EAT-26, the CBCL 6-18, the CPRS and the F.R.T. (family relation test). Results: All the patients were positive almost to one or more tests, with M:F ratio of 1:1 for anxiety scale. However psychosomatic diseases were more frequent in females, as eating disorders. Difficulties in social behaviour was more frequent in males, as the risk of drugs and alcohol abuse. Conclusions: The specialist support and the psychological follow up helped our adolescents to win the difficulties of a chronic disease and gave them the chance to meet peers and share with them their troubles. Disclosure of Interest: None declared